2023
DOI: 10.1002/ajpa.24688
|View full text |Cite
|
Sign up to set email alerts
|

BaYaka forager food sharing networks in the Congo Basin: The roles of gender homophily and kin sharing

Abstract: Objectives Food sharing is a costly form of cooperation that was likely critical to human evolutionary success, including the emergence of human's life history strategy. Food sharing in human communities may be maintained through a number of pathways, including direct dyadic reciprocity, reputation‐based processes, and kin‐biased exchange. Differences in reproductive demands, labor, and cultural norms may also result in gendered differences in cooperative networks. Here, we examine cooperative networks in egal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 88 publications
2
7
0
Order By: Relevance
“…In a context of high marital instability, where divorced women must depend on their natal lineage for support, such strategic reckoning allows for tensions between matrikin, patrikin and in-laws to be resolved, as Goldman [81] proposes. Taken together, the importance of gender for patterning relational wealth in present study contributes to an emerging literature on gender differences (and similarities) in cooperation in rural communities [95,96] (c) The linkage between relational wealth and material wealth…”
Section: (B) Gendered Patterns Of Relational Wealthsupporting
confidence: 53%
“…In a context of high marital instability, where divorced women must depend on their natal lineage for support, such strategic reckoning allows for tensions between matrikin, patrikin and in-laws to be resolved, as Goldman [81] proposes. Taken together, the importance of gender for patterning relational wealth in present study contributes to an emerging literature on gender differences (and similarities) in cooperation in rural communities [95,96] (c) The linkage between relational wealth and material wealth…”
Section: (B) Gendered Patterns Of Relational Wealthsupporting
confidence: 53%
“…Accordingly, we were able to estimate whether the probability of observing associations was higher between adults of the same or different sexes (see Redhead, McElreath et al, 2023; Ross et al, 2023, for detailed technical outlines). To aid in interpretation of the results, we computed the contrast coefficient ∆ and highest posterior density intervals ( HPDI ) from the posterior distribution of the age/sex parameters included in our stochastic blockmodel (reflecting how such models have been interpreted in previous research, e.g., Gettler et al, 2023, Redhead, Ragione et al, 2023). ∆ represents the estimated change in the probability of observing associations between individuals of a given age/sex category (e.g., between female adults and male adults) in comparison to the probability of observed association between adult males (i.e., the reference group).…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, although there is significant evidence supporting predictions drawn from sexual selection theory across human societies [2830], socio-ecological environments and institutions have important effects on expressed differences between men and women [3133]. For example, our research group has found gender ‘reversals’ in health outcomes, where measures of matrilineal women's health were better than men's [31].…”
Section: Introductionmentioning
confidence: 94%